Output-Based Aid in the Philippines : Improved Access to Water Services for Poor Households in Metro Manila - Menzies, Iain (World Bank, Washington, DC, 2012)
This project aims to provide access to water services through individual household connections to several low-income communities in Rizal province (Antipolo City, Baras, Rodriguez, and San Mateo) and Taguig city in the Manila Metropolitan region through collaboration with the concessionaire for Manila's east zone, the Manila Water Company (MWC). The GPOBA intervention supports Manila Water's flagship program, launched in 1998, the 'Water for the Community' or Tubig Para sa Barangay (TPSB) program, which provides a regular supply of clean, safe, and affordable drinking water to the urban poor. The scheme builds on the successful track record of the TPSB program and seeks to speed up rollout of individual connections to poor households through one-time subsidies to cover the cost of the connection fee.